Employment effects of business dynamics: Mice, Gazelles and Elephants - Zoltán J. Ács; Pamela Mueller (Max Planck Institute of Economics, 2006)
This paper examines the relationship between business dynamics and employment effects in 320 U.S. Metropolitan Statistical Areas (MSA). Much of the theoretical work on industry dynamics focuses on the role of noisy selection and incomplete information on entry and survival. We extend this research by looking at the impact of firm heterogeneity on employment persistence. We find that only start-ups with greater than twenty employees have persistent employment effects over time and only in large diversified metropolitan regions. Therefore, both the type of entry and the characteristics of the region are important for employment growth.
Keywords: J6; L6; L8; M13; 330; Industry dynamics; new business formation; employment effects; regions; Unternehmensgründung; Markteintritt; Betriebsgröße; Beschäftigungseffekt; Regionalökonomik; Kommunale Wirtschaftsentwicklung; USA